EFEKTIVITAS PROGRAM BANTUAN RUMAH SEHAT LAYAK HUNI (RSLH) ( STUDI KASUS DI DESA BUKIT GAJAH KECAMATAN UKUI KABUPATEN PELALAWAN) - Helda Yanti; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The fulfillment of housing needs is the right of every citizen, because it is guaranteed by the 1945 Constitution in Article 28H Paragraph 1 which states that "everyone has the right to live in physical and spiritual prosperity, to live. , and has a good and healthy living environment and has the right to health services. . Based on the Constitution, the Government organizes a Healthy Home Assistance Program which is given to underprivileged communities who do not have a home or already have a house that is not suitable for habitation. The purpose of this study was to determine the effectiveness of the Healthy Home Assistance Program in Bukit Gajah Village, Ukui District and the factors the obstacle. This research uses purposive sampling technique with case study method and data needs, both primary data and secondary data obtained through observation, interviews, and documentation, for further analysis. implementation of the healthy housing assistance program. This program is still not right on target that should have been received but not received, this is due to several factors such as cooperation and lack of coordination. Keyword : Effectiveness, Program, Habitable House